An Empirical Investigation of the Demand for Bank‐Owned Life Insurance. Issue 5 (December 2014) - Davidson, Travis R.; Shelor, Roger M.
<x xml:space="preserve">Abstract</x> Key employee life insurance in the banking industry is called bank‐owned life insurance (BOLI). Banks use BOLI to provide financial support to help reduce disruptions due to the death of a key executive and as a part of the executive compensation package. We investigate the characteristics of banks related to the amount of BOLI purchased. We find that BOLI purchases are positively related to bank size and leverage and negatively related to tax rates and employee salaries. We also find that BOLI purchases are related to bank ownership structure and profitability.